From Islamism to Democracy: The Case of Rached Ghannouchi and Ennahda of Tunisia - Ahmad Nur Fuad; Slamet Muliono Redjosari; Rofhani Rofhani (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
This article examines the shift of Rached Ghannouchi and Ennahda party from Islamism to democracy. This article analyzes Ghannouchi’s early Islamist ideology and confrontational approach to politics, as well as his exposure to democratic systems, which led to a reevaluation of his views on democracy, following the failure of Ennahda’s early attempts at revolutionary Islamism in the 1980s and 1990s, which prompted Ghannouchi to reconsider his approach to politics and Islamism. This led to a shift towards a more moderate and inclusive approach to politics, culminating in Ennahda’s participation in Tunisia’s democratic transition after the 2011 revolution. This article highlights the theoretical implications of his shift from Islamism to democracy for the study of political Islam and democratization. This article argues that Islamist actors and movements can evolve and adapt to changing political circumstances, as well as undergo gradual moderation in promoting democratic reform.